Study of the Bacterial, Fungal, and Archaeal Communities Structures near the Bulgarian Antarctic Research Base “St. Kliment Ohridski” on Livingston Island, Antarctica - Vesselin V. Doytchinov; Slavil Peykov; Svetoslav G. Dimov (Life, 2024)
As belonging to one of the most isolated continents on our planet, the microbial composition of different environments in Antarctica could hold a plethora of undiscovered species with the potential for biotechnological applications. This manuscript delineates our discoveries after an expedition to the Bulgarian Antarctic Base “St. Kliment Ohridski” situated on Livingston Island, Antarctica. Amplicon-based metagenomics targeting the 16S rRNA genes and ITS2 region were employed to assess the metagenomes of the bacterial, fungal, and archaeal communities across diverse sites within and proximal to the research station. The predominant bacterial assemblages identified included Oxyphotobacteria, Bacteroidia, Gammaprotobacteria, and Alphaprotobacteria. A substantial proportion of cyanobacteria reads were attributed to a singular uncultured taxon within the family Leptolyngbyaceae. The bacterial profile of a lagoon near the base exhibited indications of penguin activity, characterized by a higher abundance of Clostridia, similar to lithotelm samples from Hannah Pt. Although most fungal reads in the samples could not be identified at the species level, noteworthy genera, namely Betamyces and Tetracladium, were identified. Archaeal abundance was negligible, with prevalent groups including Woesearchaeales, Nitrosarchaeum, Candidatus Nitrosopumilus, and Marine Group II.